Mewujudkan Lingkungan Bersih dan Hijau melalui Gerakan Edukasi Informasi untuk Kelurahan yang Berkelanjutan - Solong, Aras; Aras Solong (Journal Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Community service is an activity carried out as a form of student service to the community in order to provide learning experiences about community development and real work experience to achieve community welfare. Providing students with experiences about the conditions that exist in the community and how to live in the community by implementing the disciplines they have learned through lectures can also improve relations between universities and sub-district governments, village governments, and the community directly. Meanwhile, for the community, the presence of KKN students will provide guidance in addressing various issues and challenges faced, such as in the fields of education, health, employment, and the environment